Effect of host tree site conditions of Schima wallichii on vertical structure of epiphytic orchid community - INDRA FARDHANI; YUDAI KITAGAMI; TAKESHI TORIMARU; HIROMITSU KISANUKI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Fardhani I, Kitagami Y, Torimaru T, Kisanuki H. 2025. Effect of host tree site conditions of Schima wallichii on vertical structure of epiphytic orchid community. Biodiversitas 26: 715-722. It is crucial to recognize the conservation challenges and potential intertwined with the delicate balance of epiphytic orchid communities. Therefore, it is imperative to deepen our understanding regarding the factors influencing the ecology of epiphytic orchid community, including how orchid diversity is distributed on a host tree. To clarify the variation in vertical community structure of epiphytic orchids on a host tree species, Schima wallichii, species richness and abundance of these orchids were investigated. Epiphytic orchids occurring on each host tree were allocated to one of five vertical zones. To understand their effects on community structures, host tree site factors such as density of trees surrounding the host, and angle and direction of slope on which the host tree stood, were measured. Crown zones of S. wallichii trees accumulated more species of epiphytic orchids than the trunk zone because the crown contains many branches, to which epiphytes can attach more easily than on the trunk. Zone 3, at the bottom of the crown zone, offered the most potential for many kinds of epiphytic orchid to colonize, according to the accumulation curves of species richness against both the number of host trees and orchid abundance; this is probably because it had larger branches than the other crown zones. The vertical community structures of epiphytic orchid on S. wallichii were not clearly segregated, even between trunk and the three crown zones. Host tree angle of slope significantly drove the vertical structure of the epiphytic orchid community.